Closing the Gap: Collaborating with Research Librarians to Improve Information Literacy in the Political Science Classroom. Issue 4 (2nd October 2021) - Devine, Christopher J.; Gauder, Heidi; Pautz, Michelle C.
Abstract: This article discusses a collaborative effort between political science faculty members and a research librarian, designed to determine whether structured library interventions with students over the course of a semester yield improvement in students' information literacy skills. Using the ACRL Framework for Information Literacy for Higher Education as the basis for an information literacy pre- and post-test, faculty conducted a two-wave survey of students enrolled in political science courses, taken at the beginning and end of a semester, while the librarian taught an information literacy session with select political science courses. We then compared the survey results to measure information literacy gains of all students. The results reinforce findings from other studies that collaborating with a research librarian contributes positively to student learning, and the methodology used to evaluate information literacy gains here can be used to provide additional assessment in the future.